2011
DOI: 10.1590/s1676-06032011000500023
|View full text |Cite
|
Sign up to set email alerts
|

Checklist dos Copepoda Cyclopoida de vida livre de água doce do Estado de São Paulo, Brasil

Abstract: Estudo da biodiversidade de Copepoda Cyclopoida do Estado de São Paulo foi feito no Programa BIOTA/FAPESP, amostrando 207 corpos de água das 22 Unidade de Gerenciamento de Recursos Hídricos (UGRHI). Foram registradas 39 espécies englobando tanto espécies de hábito planctônico como de hábito não planctônico. Destas, 6 espécies constituem registro novo no Estado de São Paulo sendo uma espécie nova, o Thermocyclops iguapensis, espécie restrita na costa Atlântica (Silva & Matsumura-Tundisi 2005a). Foram realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…Of the 39 species of Cyclopoida recorded in São Paulo State (Silva & Matsumura-Tundisi 2011) only nine were dominant in any reservoir (in the pelagic zone) and of these, only seven were dominant in more than five reservoirs. It should, nevertheless, be pointed out that some authors have recorded other species not observed in the present work, such as Metacyclops mendocinus, as dominant, in eutrophic systems (Sendacz & Kubo 1982, Arcifa 1984, Tundisi & Matsumura-Tundisi 1990.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 39 species of Cyclopoida recorded in São Paulo State (Silva & Matsumura-Tundisi 2011) only nine were dominant in any reservoir (in the pelagic zone) and of these, only seven were dominant in more than five reservoirs. It should, nevertheless, be pointed out that some authors have recorded other species not observed in the present work, such as Metacyclops mendocinus, as dominant, in eutrophic systems (Sendacz & Kubo 1982, Arcifa 1984, Tundisi & Matsumura-Tundisi 1990.…”
Section: Discussionmentioning
confidence: 97%
“…Both endemic microcrustacean Daphnia laevis [49] and Mesocyclops sp. [50] have been reported in other upstream reservoirs. SAR (Stramenopila, Alveolata, and Rhizaria) organisms belonging to Stramenopila clade were not identified beyond this level, probably because the lack of reference sequences hampers a reliable taxonomic identification of this group [51].…”
Section: Resultsmentioning
confidence: 94%
“…A classe Bacillariophyceae teve a listagem feita para o estado do Paraná analisando mais de 50 anos de registros distribuídos em 88 trabalhos, contabilizando 1004 táxons (Tremarin et al 2009). Silva et al (2011) registrou 503 táxons para a região centro-oste, incluindo 23 espécies no estado do Mato Grosso do Sul, e com os dois trabalhos específicos da classe realizados por Temarin et al (2013Temarin et al ( , 2014 este número foi acrescido de duas novas espécies, totalizando 25 espécies para o estado. A classe Zygnemaphyceae, possui 2700 espécies catalogadas no mundo (Reviers 2006).…”
Section: Resultsunclassified